Cryptocurrency and Global Remittance Dynamics: An Empirical Analysis - Altaf, Suleiman (2026)
A Master of Science in Economics and Policy (MSEP) by Suleiman Altaf entitled, “Cryptocurrency and Global Remittance Dynamics: An Empirical Analysis”, submitted in May 2026. Thesis advisor is Dr. Samer Kherfi. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).